Nonhuman Animal Agency: Human and Free-Roaming Cats’ Coexistence in Spinut Neighbourhood in Split, through an Interdisciplinary Artistic Practice - Filip, Ivana (Poznańskie Studia Slawistyczne, 2022)
This artistic research was a one-year Master Performing Public Space program at Fontys School of Fine and Performing Arts in Tilburg, Netherlands. Based on concepts of coexistence between nonhumans and humans, it creates new narratives with the models of utopia, symbiocene, empathy. The author, while observing a community of free-roaming cats, co-created a series of interspecies communication and utopian experiments with humans and cats. The work is inspired by the author’s close intertwining with nonhumans and continues her artistic practice based in anthrozoology. It exemplifies artistic co-creation with nonhumans, more-than-human public space geography and the potential of artistic research as a scientific discipline.